The pediatric precision oncology INFORM registry: clinical outcome and benefit for patients with very high-evidence targets - Tilburg, Cornelis M. van; Pfaff, Elke; Pajtler, Kristian Wilfried; Langenberg, Karin; Fiesel, Petra; Jones, Barbara Christine; Balasubramanian, Gnana Prakash; Stark, Sebastian; Johann, Pascal-David; Blattner-Johnson, Mirjam; Schramm, Kathrin; Dikow, Nicola; et al. (Cancer discovery, 2021)
INFORM is a prospective, multi-national registry gathering clinical and molecular data of relapsed, progressive or high-risk pediatric cancer patients. This report describes long-term follow-up of 519 patients in whom molecular alterations were evaluated according to a pre-defined 7-scale target prioritization algorithm. Mean turnaround time from sample receipt to report was 25.4 days. The highest target priority level was observed in 42 patients (8.1%). Of these, twenty patients received matched targeted treatment with a median PFS of 204 days (95% CI 99 - N.A.), compared with 117 days (95% CI 106 - 143; P=0.011) in all other patients. The respective molecular targets were shown to be predictive for matched treatment response and not prognostic surrogates for improved outcome. Hereditary cancer predisposition syndromes were identified in 7.5% of patients, half of which were newly identified through the study. Integrated molecular analyses resulted in a change or refinement of diagnoses in 8.2% of cases.
Gesehen am 30.07.2021